Evaluating the success factors of Information Systems (IS) -case study of Malaysian public sector - Fuad Zamzami, Ikhlas; Phoesalaeh, Basiyah; Hayiyusoh, Nur-Adib; Ahmad Dahlan, Abdul Rahman (2011)
Managing and implementing project well is important issues for IS projects in the public sector as well as other sectors. The government tasks the public sector to use public resources to deliver large and complex projects for the benefit of its citizens. Information and communications technologies (ICTs) are playing an increasingly vital role in the daily lives of people, revolutionizing work and leisure and changing the rules of doing business. However, still there is a gap between reality and achievement the success. This paper aims to evaluating the success factors of information system (IS) projects implementation in Malaysian government sector focusing on the correlated of project success criteria including Processes, People, Project Tools (Hardware and Software) and Project environment. The proposed model of project success criteria will be introduced and discussed.